Pendampingan Masyarakat Kota Serang Dalam Pendampingan Pro dan Kontra Terhadap Vaksinasi Covid-19 - Nining Zahrotul Uyun; Nining Farida; Nulfa Dwi Maulidia; Nunung Nurohmah; Nelis Yulandari Fadilah; Masykur Masykur (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2021)
Abstract: The Indonesian government's policy to vaccinate Covid-19 to its citizens during the pandemic generates pro and contra views. In community assistance, this community service will express the views of the pro and contra in the community of Serang City of Banten Province. There are two questions that are the focus of community service. First, how is the understanding of the people of Serang city regarding Covid-19 vaccination? Second, what is the public's view of Covid-19 vaccination? These two focuses are aimed at explaining people's understanding of Covid-19 vaccination and explaining the views of the people of Serang City towards Covid-19 vaccination. For that, used methods of description, literature studies and case studies. It found that there were 14 people with pro views and 11 people with counter-views towards Covid-19 vaccination. However, through the assistance of Covid-19 health procedures education, the public becomes more understanding of Covid-19 vaccination. As a result, 4 out of 11 people who countered became convinced of the Covid-19 vaccination for herd immunity. Kebijakan pemerintah Indonesia untuk melakukan vaksinasi Covid-19 kepada warga negaranya pada masa pandemi menghasilkan pandangan pro dan kontra. Dalam pendampingan masyarakat, pengabdian kepada masyarakat ini akan mengungkapkan pandangan pro dan kontra di dalam masyarakat Kota Serang Provinsi Banten. Ada dua pertanyaan yang menjadi fokus pengabdian kepada masyarakat. Pertama, bagaimana pemahaman masyarakat Kota Serang mengenai vaksinasi Covid-19? Kedua, bagaimana pandangan masyarakat terhadap vaksinasi Covid-19? Dua fokus ini ditujukan untuk menjelaskan pemahaman masyarakat mengenai vaksinasi Covid-19 dan penjelasan pandangan masyarakat Kota Serang terhadap vaksinasi Covid-19. Untuk itu, digunakan metode deskripsi, studi pustaka dan studi kasus. Ditemukan bahwa ada 14 orang berpandangan pro dan 11 orang berpandangan kontra terhadap vaksinasi Covid-19. Namun, melalui pendampingan edukasi prokes Covid-19, masyarakat menjadi lebih memahami vaksinasi Covid-19. Hasilnya, 4 dari 11 orang yang kontra menjadi yakin terhadap vaksinasi Covid-19 untuk herd immunity. Vaksinasi Covid-19, Pandangan Pro dan Kontra, Herd Immunity